Wheelchair rugby chair configurations: an individual, robust design approach - Haydon, D. S.; Pinder, R. A.; Grimshaw, P. N.; Robertson, W. S. P. (Sports Biomechanics, 2022)
Prescription of wheelchair rugby chairs is difficult due to the range of athlete impairment types and severities in the sport, difficulty in adjusting wheelchair settings, and assessing on-court performance. Currently, elite players rely on experiential knowledge (personal, coaches, and support staff) to select an appropriate set-up. Technological advancements, such as with inertial measurement units and processing algorithms, and representative testing approaches, has improved the potential for assessing set-ups at an individual level. An orthogonal design approach was implemented using an adjustable wheelchair to investigate the effect of seat height, seat depth, seat angle, and tyre pressure on performance, mobility, and propulsion kinematics. Six elite wheelchair rugby players completed testing in nine individually tailored wheelchair set-ups while monitoring both quantitative and qualitative measures of performance. From this testing, a recommended set-up was compared with the current set-up for each individual. A single case-study approach shows how the assessment method identifies parameter settings that can potentially improve performance. Three of six players reported a blind preference for the recommended set-up over the current set-up, whilst remaining players often displayed similar performance between their current and recommended set-ups. This approach can improve upon the current prescription process for rugby wheelchairs.